Early detection of autism: comparison of two screening tools - Darne, Sachin (International Journal of Research in Medical Sciences, 2016)
Background: The aim of the study was comparison of a newly developed test called Trivandrum Autism Behavioural Checklist (TABC) with gold standard test; Checklist for Autism in Toddlers (CHAT). Methods: The study was done on 200 children over a period of three months between age group of 24 to 36 months. All the children were briefly evaluated for history and then the two tests were administered by two doctors. Results: It was found that out of total 200 children only 3 children were suspected to have autism by the CHAT test and they failed in the scores by having more number of “no” answers. It was also observed that the same 3 children were also detected to have autism by the TABC scores in which one girl was suspected to have severe autism while two boys seemed to have mild to moderate autism. The prevalence of autism as per this study was seen to be around 1.5%. Conclusions: Thus it can be inferred from this study that TABC test is an equally good option for screening children for autism.